Factors Controlling Stress Generation during the Initial Growth of Porous Anodic Aluminum Oxide. (20th March 2015) - Çapraz, Ömer Özgür; Shrotriya, Pranav; Skeldon, Peter; Thompson, George E.; Hebert, Kurt R.
Highlights: Anodizing produced significant stress both in the oxide and at the metal-oxide interface. Stress generation at a given interface of the anodic film correlates with volume change at the interface produced during anodizing. A simple criterion specifies the conditions for compressive stress generation in anodic oxides, which is believed to necessary for formation of self-ordered arrangements of pores. Abstract: Anodic oxidation of reactive metals such as Al and Ti produces oxide films with self-organized arrangements of nanoscale pores. Stress-driven mass transport of oxide is considered to play an important role in pore formation and self-ordering. Using in situ stress monitoring during both anodizing and subsequent open-circuit oxide dissolution, distributions of in-plane residual stress were measured in anodic alumina films formed by galvanostatic anodizing in phosphoric acid. Anodizing produced significant stress both in the oxide and at the metal-oxide interface. For oxides grown to 20 nm thickness, the oxide stress was tensile below 3 mA/cm 2 and compressive above this current density, while the interface stress exhibited the opposite dependence. Stress generation correlated with interfacial volume change due to reactions and transport processes: oxide or interface stress was compressive when interfacial volume was created, and vice versa. Compressive stress buildup in the oxide is apparently required for self-ordered pore formation by flow-assisted mechanisms. From the present results, a simple criterion was derived specifying the conditions for compressive stress and pore formation in terms of parameters governing film composition, ionic transport and interfacial reaction kinetics.